Red sacaca essential oil-loaded nanostructured lipid carriers optimized by factorial design: cytotoxicity and cellular reactive oxygen species levels - Chura, Sofia Santos Donaire; Memória, Kathelen Anne Sudo; Lopes, Amanda Tibães; Pelissari, Franciele Maria; Da Silveira, João Vinícios Wirbitzki; Bezerra, Jaqueline de Araújo; Chaves, Francisco Celio Maia; Rodrigues, Ana Paula; Faria, Jerusa Araújo Quintão Arantes; Carneiro, Guilherme (Frontiers in Pharmacology, 2023)
Amazonian flora includes several species with the potential to develop pharmaceutical and biotechnological products. The essential oils from Amazonian species possess some biological properties, such as antioxidant, antibacterial, and cytotoxic activities. The essential oil of red sacaca (RSO), Croton cajucara Benth., contains metabolites characterized by antioxidant and antiinflammatory activities. Nanostructured lipid carriers (NLC) are an advantageous alternative for the effective delivery of drugs because they can solubilize lipophilic actives and reduce their cytotoxicity. This study aimed to optimize the synthesis of RSO-loaded nanostructured lipid carriers (NLC-RSO) using a 2 3 factorial design and investigate their antioxidant and cytotoxic effects. The red sacaca essential oil (RSO) metabolite profile was characterized using gas chromatography coupled with a mass spectrometer (GC-MS), identifying 33 metabolites, with linalool and 7-hydroxy-calamenene as the major ones, as reported in the literature. The optimized NLC-RSO formulation had a particle size less than 100 nm and a polydispersity index lower than 0.25. After characterizing NLC-RSO using Fourier-transform infrared spectroscopy, powder X-ray diffraction, zeta potential, moisture content, and wettability, in vitro cytotoxicity were performed in A549 and BEAS-2B cell lines using the resazurin metabolism assay. The data indicated a lower IC50 for RSO than for NLC-RSOs in both cell lines. Furthermore, low cytotoxicity of blank nanoparticles (blank NP) and medium chain triglyceridesloaded nanostructured lipid carriers (NLC-MCT) towards both pulmonary cell lines was noted. At a concentration of 50-100 μg/mL, free RSO exhibited higher cytotoxicity than NLC-RSO, demonstrating the protective effect of this lipid carrier in reducing cytotoxicity during metabolite delivery. Similarly, free RSO showed higher 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging than NLC-RSO, also indicating this protective effect. The 2',7'-dichlorofluorescein diacetate (DCFH-DA) intracellular reactive oxygen species (ROS) level assay did not show differences between the treatments at higher but non-cytotoxic dosages. Taken together, our results suggest that NLC-RSOs are potential RSO delivery systems for applications related to cancer treatment.